A review of hydrodeoxygenation of bio-oil: model compounds, catalysts, and equipment. Issue 23 (19th November 2021) - Qu, Lu; Jiang, Xia; Zhang, Zihao; Zhang, Xiang-gang; Song, Guo-yong; Wang, Hua-lin; Yuan, Yuan-ping; Chang, Yu-long
Abstract : Bio-oils are an important part of the future energy composition. Abstract : Bio-oils are an important part of the future energy composition. This review primarily focuses on model compounds, catalysts, and equipment involved in the hydrodeoxygenation (HDO) of bio-oils. Initially, this article reviews the basic physicochemical properties of bio-oils and introduces different upgrading methods. Among them, HDO can effectively facilitate calorific value and improve the acidity and viscosity of bio-oils. Secondly, the basic HDO reaction pathways and proposed catalytic mechanism of various model compounds are summarized to understand the catalytic behavior and structure–performance relationship of the HDO reaction. Subsequently, we review different catalysts used in actual HDO of bio-oils, some of which lead to excellent stability and improved HDO reactivity. Finally, progress in the development of HDO equipment, including fixed bed and ebullated bed reactors in the pilot stage, is reviewed. This review aims to summarize progress in the utilization of the HDO process and provides useful insights for the efficient practical application of bio-oils.